Expression of IFN‐induced transmembrane protein 1 in glomerular endothelial cells. Issue 9 (29th July 2021) - Hashimoto, Shun; Imaizumi, Tadaatsu; Watanabe, Shojiro; Aizawa, Tomomi; Tsugawa, Koji; Kawaguchi, Shogo; Seya, Kazuhiko; Matsumiya, Tomoh; Tanaka, Hiroshi
Abstract: Background: Glomerular endothelial cells (GECs) are directly exposed to circulating viral particles in the glomerulus. Although viral infections may trigger the development of acute kidney injury or the worsening of pre‐existing chronic kidney disease, the specific molecular mechanisms underlying antiviral reactions via the activation of endothelial Toll‐like receptor 3 signaling in the kidney remain to be determined. Interferon (IFN)‐induced transmembrane protein 1 (IFITM1), a member of interferon‐stimulated gene protein family, is involved in the prevention of viral entry into cerebral vascular endothelial cells, respiratory epithelial cells, and endometrium. However, as far as we are aware, the implication of IFITM1 associated with viral infections in GECs has not been investigated to date. Methods: Cultured, normal human GECs were treated with polyinosinic‐polycytidylic acid (poly IC), a synthesized viral double‐stranded RNA, then the expression of IFITM1 was examined by quantitative real‐time reverse transcription‐polymerase chain reaction and western blotting. To further elucidate the poly IC‐induced signaling pathway, the cells were applied to RNA interference against IFN‐β, nuclear factor‐κB p65, and IFN regulatory factor 3. We also conducted an immunofluorescence study to examine endothelial IFITM1 expression in biopsy specimens from patients with chronic kidney disease. Results: We found that the activation of Toll‐like receptor 3 induced endothelial expression of IFITM1, and that this involved IFN regulatory factor 3 and IFN‐β, but not nuclear factor‐κB. Intense endothelial IFITM1 immunoreactivity was observed in biopsy specimens from patients with lupus nephritis. Conclusions: Antiviral reaction‐related endothelial expression of IFITM1 may be involved, at least in part, in the development of particularly in lupus nephritis. Further detailed studies of the implication of interferon stimulated genes, including IFITM1 in GECs are needed.